Characterization of toxic metals in tobacco, tobacco smoke, and cigarette ash from selected imported and local brands in Pakistan - Ajab, H. (2014)
In this study, concentrations of Cd, Ni, Pb, and Cr were determined in tobacco, tobacco smoke-condensate, and cigarette ash for selected brands used in Pakistan. Smoking apparatus was designed for metal extraction from cigarette smoke. Samples were digested through microwave digester and then analyzed by flame atomic absorption spectrophotometer (FAAS). Higher concentration of Ni was detected in imported brands than the counterparts in the local brands. Pb levels were however higher in local brands while significant concentration of Cd was observed in both brands. For Cr, the level in tobacco of local brands was higher than their emitted smoke, whereas imported brands showed higher level in smoke than in tobacco. The cigarette ash retained 65 to 75 of the metal and about 25 to 30 went into the body. While this study revealed the serious requirement to standardize the manufacturing of tobacco products, more importantly is the urgent need for stronger enforcements to put in place to alert the general population about the hazardous effects of cigarettes and the health risks associated with these toxic metals. Â© 2014 Huma Ajab et al.